Ethical Issues of Fair Subject Selection in the Research (Bangladesh Journal of Bioethics, 2015)
Ethics and ethical principles extend to all spheres of human activity. They apply to our dealings with each other, with animals and the environment. They should govern our interactions not only in conducting research but also in commerce, employment and politics. Ethics serve to identify good, desirable or acceptable conduct and provide reasons for those conclusions. Fair subject selection is the first and foremost concern which must be ensured before initiating a research project.  Which subjects may enroll in the research is determined by the studys inclusion or exclusion criteria. One of the important aspects of fair subject selection is to have an oversight system through International Review Board (IRB) to review to conduct the research and to have approval whether subject selection is fair or not.